O Conselho Nacional de Justiça e a cultura política brasileira : entre o controle do estado e o poder nas relações sociais. - Oliveira, Vitor Costa (2011)
This work aimed discussing the political culture and the law field in Brazil, by the analysis of Conselho Nacional de Justiça (CNJ), a state structure created through constitucional amendment nº 45/04 and idealized for the accomplishment of administrative control and fiscalization of judiciary power. The research tried to indentify if the performance and results of CNJ is linked to a movement witch seems to improve social e state institutions witch work wth the ideas of counting, transparency and real punition for public agents whom deviate from the public interest, descriptions that take us to the term accountability. Also, the work sought to comprehend the way how has been always showed up the relationship of brazilian society with power, images usually linked to the notions of privileges, and construction of social hierarchies, and, in this theoretical kick-off, introducing an analysis of control of power in this point of view. For obtaining results, was listened five counselors, a judge and two members from the statistic sector. Yet, we visited a public audience promoted by CNJ, at Recife, where it was possible to take notes about the significance and relevance of the meeting, and also interview some of the people there. It was made a analysis of normative texts edited by CNJ and inspection reports, emphasizing the administrative control aspects. The work has also studied the law field, aiming a panoramic view of this arena, its disputes, its agents, and objects in dispute. Because CNJ members are always people related to law field, this fact pushed into a specifically research of this space. The results pointed to a possible change in the reality of brazilian judiciary service considering the performance of CNJ in its beginning. At first, CNJ tried to elaborate a map, a panoramic view of the problems in judiciary and, with the informations in its hands, converged efforts for solutions. This diagnosis was able to conclude that there was no idea or spirit of a public service and, much less, of professional public management, at brazilian judiciary. The normative texts edited by CNJ as resolution nº 07/05, witch has made illegal the nepotism, and also the resolution 75/09, witch disciplines the concession of daily incomes for trips, for example comes as reaction to a complete absence of control that as the conclusions pointed has never existed at that power. The analysis suggests that CNJ can be considered an accountability public agency, and considering a more abstract theoretical view, that, its performance (into a social e historical context) might reflect a social change about the conception of power and social hierarchies.